2019
DOI: 10.1080/17435390.2018.1553252
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Toxicity Assessment of Silver Nanoparticles in Homeostatic versus Regenerating Planarians

Abstract: Silver nanoparticles (AgNPs) currently belong to the most commercialized nanomaterials, used in both consumer products and medical applications. Despite its omnipresence, in-depth knowledge on the potential toxicity of nanosilver is still lacking, especially for developing organisms. Research on vertebrates is limited due to ethical concerns, and planarians are an ideal invertebrate model to study the effects of AgNPs on stem cells and developing tissues in vivo, as regeneration mimics development by triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 71 publications
0
24
1
2
Order By: Relevance
“…It has been reported that changes in physicochemical properties of AgNPs affect their toxicity and neuroregeneration capacity. In an interesting example, Leynen et al examined non-coated AgNPs and polyvinylpyrrolidone (PVP)-coated AgNPs (30 nm in diameter) on neurodevelopment in the freshwater flatworm Schmidtea Mediterranea (Leynen et al 2019). They found that the lowest non-coated AgNPs exposure led to a markedly larger relative brain ganglia size, relative to the nonexposed worms.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that changes in physicochemical properties of AgNPs affect their toxicity and neuroregeneration capacity. In an interesting example, Leynen et al examined non-coated AgNPs and polyvinylpyrrolidone (PVP)-coated AgNPs (30 nm in diameter) on neurodevelopment in the freshwater flatworm Schmidtea Mediterranea (Leynen et al 2019). They found that the lowest non-coated AgNPs exposure led to a markedly larger relative brain ganglia size, relative to the nonexposed worms.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Likewise, the authors mentioned that 59% of the PVP-AgNP-exposed worms showed partial eye regeneration (33%) while disruption of eye regeneration occurred in 24% of non-coated AgNPsexposed worms. Finally, they concluded that physicochemical properties and concentration of AgNPs significantly influence their regenerative capacity and toxicity (Leynen et al 2019).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…La planaire a également été utilisée pour étudier l'impact de nanoparticules d'argent, des nanomatériaux largement répandus dans des produits de consommation courante mais aussi dans des applications médicales, dont la toxicité reste encore méconnue. Récemment, une étude a mis en évidence une forte influence de ces nanoparticules sur la régénération de la planaire Schmidtea mediterranea avec, notamment, un retard d'apparition des taches oculaires et une altération significative de la prolifération des cellules souches pour des fragments de tête en régénération [24].…”
Section: Toxicité Des Métaux Et Des Dérivés Organométalliquesunclassified